Global stability of a class of discreteage-structured SIS models with immigration - Yicang Zhou; Zhien Ma (Mathematical Biosciences and Engineering)
Immigration has an important influence on the growth of populationand the transmission dynamics of infectious diseases. A discreteage-structured epidemic SIS model with immigration is formulated andits dynamical behavior is studied in this paper. It is found thatpopulation growth will be determined by the reproductive numberand the immigration rate. In the simple case without infectedimmigration, the basic reproductive number is defined, and theglobal stability of equilibria is investigated. In the case withinfected immigration, there is no disease-free equilibrium, andthere always exists an endemic equilibrium, and the global stabilityconditions of the unique endemic equilibrium is obtained.